Image of Uma Maheshwar inside a niche - Temples of India Project Team (Jio Institute, 2024)
A figure of Uma Maheshwar inside a niche. Shiva is seated in the lalitasana posture, while Parvati is comforted in his lap. It is affixed on a late structure.